2004
DOI: 10.1038/sj.onc.1207417
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat increases cell survival in response to cisplatin by stimulating Rad51 gene expression

Abstract: Tat is an early regulatory protein of human immunodeficiency virus type 1, which plays a central role in the pathogenesis of AIDS by stimulating transcription of the viral genome and impairing several important cellular pathways during the progression of the disease. Here, we investigated the effect of Tat on cell response to DNA damage. Our results indicate that Tat production causes a noticeable increase in the survival rate of PC12 cells upon their treatment with genotoxic agents. Single-cell gel electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…The histone acetyltransferase HTATIP (HIV-1 Tat interactive protein, 60 kDa), postmeiotic segregation increased 2-like 6 (PMS2L6), general transcription factor IIH, polypeptide 1 (GTF2H1), and the DNA ligase LIG4, showed higher levels of expression in cell lines that are more resistant to oxaliplatin treatment. In fact, at least LIG4 has been shown previously to confer resistance to the related platinum compound cisplatin (Chipitsyna et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The histone acetyltransferase HTATIP (HIV-1 Tat interactive protein, 60 kDa), postmeiotic segregation increased 2-like 6 (PMS2L6), general transcription factor IIH, polypeptide 1 (GTF2H1), and the DNA ligase LIG4, showed higher levels of expression in cell lines that are more resistant to oxaliplatin treatment. In fact, at least LIG4 has been shown previously to confer resistance to the related platinum compound cisplatin (Chipitsyna et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Our data from colorectal cancer cells indicated that the proliferation rate index (PRI) decreased significantly up to 1.49 ± 0.83 (p < 0.01) and 1.82 ± 0.22 (p < 0.001) when treated with satraplatin and oxaliplatin in the highest concentration. Interstrand crosslink repair would necessitate both nucleotide excision and recombinational repair pathways [56]. During replication, the decreased DNA synthesis is partially responsible in the chemotherapeutic effect of drugs which form bulky adducts on the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Note, however, that in the presence of cisplatin values of Olive tail moments are expectedly lower, and DNA breaks appear much later in comparison to g-irradiation induced DNA damage. 39 Further evaluation of the data in Figures 1c and 1d indicates that not only are the initial levels of DNA damage similar between BsB8 and Bs-1a cells, but the overall DNA repair seems to be unaffected by the presence of JCV T-antigen (compare ''5 min'' and ''15 min'' time points from g-irradiation; 24 and 48 hr time points from cisplatin). This was quite unexpected considering that BsB8 cells are much more sensitive to cisplatin than Bs-1a cells (Figs.…”
Section: Jcv T-antigen Sensitizes Medulloblastoma Cells To Dna Damagementioning
confidence: 99%
“…This is because intra-strand cross-links formed after cisplatin treatment partially prevent the development of typical comets despite of the fact that single and double strand breaks are also present. 39 With this in mind, we performed separate assays for g-irradiation and for cisplatin-induced DNA damage (Fig. 1d).…”
Section: Jcv T-antigen Sensitizes Medulloblastoma Cells To Dna Damagementioning
confidence: 99%